GPS and mobile application mapping for oil palm: a case study at UiTM Jasin, Melaka / Nur Hazwani Mohd Ibrahim - Mohd Ibrahim, Nur Hazwani (Faculty of Plantation and Agrotechnology, 2018)
Mobile application is one of the technology in precision farming that can utilize measurement system that have been integrated to provide three-dimensional near-continuous positioning platform and data collection using single or multiple GPS base station. Mobile application was already applied in the agricultural sector by implying the GPS software in the smartphone. Previously, mapping of oil palm per stand was done by using the GPS device. This study was conducted to compare the accuracy of GPS mapping with the mobile application mapping in the smartphone. This study was significant to the young farmer and also smallholder to imply the technology of mobile application mapping in their smartphone to get a specific information for their crops in the field. The overlap map show the accuracy of coordinate between the GPS mapping and mobile application mapping is accurate. The percentage of RMSE value from these two technologies show highly accurate because the value is 0.39 %.